B-Cell Deficiency Lowers Blood Pressure in Mice. Issue 3 (March 2019) - Dingwell, Luke S.; Shikatani, Eric A.; Besla, Rickvinder; Levy, Andrew S.; Dinh, Danny D.; Momen, Abdul; Zhang, Hangjun; Afroze, Talat; Chen, Michelle B.; Chiu, Felix; Simmons, Craig A.; Billia, Filio; et al.
Abstract : The proto-oncogene c-myb (and corresponding nuclear transcription factor, c-Myb) regulates the proliferation and differentiation of hematologic and vascular smooth muscle cells; however, the role of c-Myb in blood pressure regulation is unknown. Here, we show that mice homozygous for a hypomorphic c-myb allele ( c-myb h/h ) conferring reduced c-Myb activity manifest reduced peripheral blood and kidney B220 + B-cells and have decreased systolic (104±2 versus 120±1 mm Hg; P <0.0001) and diastolic blood pressure (71±2 versus 83±1 mm Hg; P <0.0001) compared with WT (wild type) mice. Additionally, c-myb h/h mice had lower susceptibility to deoxycorticosterone acetate-salt experimental hypertension. Although cardiac (echocardiography) and resistance artery (perfusion myography) functions were normal, metabolic cage studies revealed that c-myb h/h mice had increased 24-hour urine output and sodium excretion versus WT . Reconstitution of WT mice with c-myb h/h bone marrow transplant and chimeric bone marrow transplant using mice lacking B-cells ( J H T ; h/h>WT and h/h:J H T>WT, respectively) decreased blood pressure and increased 24-hour urine output compared with controls ( WT>WT ; WT:J H T>WT ). J H T mice also had decreased systolic (103±2 versus 115±1 mm Hg; P <0.0001) and diastolic blood pressure (71±2 versus 79±1; P <0.01) and increased 24-hour urine output versus WT . Real-time quantitative reverse transcription polymerase chain reaction of kidney medulla revealed reduced V2 R (vasopressin receptor 2) expression in c-myb h/h and J H T mice. These data implicate B-cells in the regulation of V2 R and its associated effects on salt and water handling and blood pressure homeostasis. Abstract : Supplemental Digital Content is available in the text.